What do patients expect from osteosynthetic stabilization of proximal tibial fractures?. Issue 5 (28th May 2020) - Hellinger, Lena; Keppler, Alexander M.; Ihle, Christoph; Stuby, Fabian; Saier, Tim
Aims and Objectives: Surgical treatment of proximal tibial fractures is often associated with complications and postoperative limitations in knee motion. Unrealistic patient expectations of the operation may lead to dissatisfaction with the surgical outcome despite successful surgery. The hypothesis of this study was that patients with proximal tibial fracture have very high expectations of surgical intervention in terms of painlessness, return to work and sport ability. Further, underestimation of the risk for the development of secondary gonarthrosis was hypothesized. Materials and Methods: From 2017-2018, n=79 patients (n=35 w, mean age 48 years ±13.6 years) with proximal tibial fracture were prospectively and consecutively enrolled at three level A trauma centers. Preoperatively, demographic data, fracture classification according to AO classification, the HSS -Knee Surgery Expectations Survey using the 4-point Likert scale, the workload according to REFA criteria and the non-standardized expectations regarding the return to work/sport ability and the secondary risk for developing gonarthrosis were collected and analysed. A statistical significance of p<0.05 was assumed. Results: 81% (n=63) of the patients expect a maximum duration of incapacity for work of 12 weeks regardless of age, gender and workload (n.s.). 74% (n=58) expect a return to work and 70% (n=55) a return to sport with no or only minor restrictions. Younger patients (younger than 55 years) had significantly higher expectations of an unrestricted return to work (p=0.045) and sport (p=0.04). Gender and workload had no significant influence on this expectation (n.s.). 33% (n=26) do not expect any residual pain postoperatively, regardless of activity. Younger patients expect significantly less residual pain than older patients (p=0.03). 92% (n=73) expect a completely normal knee joint or only minor differences to a healthy knee, regardless of age, gender and workload (n.s.). At least 72% (n=57) of the patients consider an unrestricted or only slightly restricted knee function to be at least important, regardless of age, sex and workload (n.s.). 29% (n=23) of the patients, regardless of age, sex and workload (n.s.) assume that the operation prevents secondary gonarthrosis. Conclusion: The results confirm our hypothesis that patients have very high expectations of the surgical treatment of proximal tibial fractures. For younger patients in particular, an unrestricted return to sport, work and painlessness is very important. The risk assessment regarding developing secondary gonarthrosis seems unrealistic. This study should help surgeons to discuss realistic expectations and results of osteosynthetic stabilization of proximal tibial fractures with their patients in order to improve patients' satisfaction.